MENDETEKSI DAN MEMPREDIKSI KECURANGAN LAPORAN KEUANGAN : KEEFEKTIVAN FRAUD TRIANGLE YANG DIADOPSI DALAM SAS NO.99 - Putri Siska Ayu Lestari; Sudarno Sudarno (Diponegoro Journal of Accounting, 2019)
The objective of this study is to detection and prediction financial statement fraud that are analyzed by the fraud triangle adopted statement of auditing standards No.99.independent variable of this study are pressure that are proxy financial stability, external pressure, personal finance need, and financial targets. Opportunity that are proxy nature of industry and ineffective mnitoring. And rationalization. This study used secondary data from annual report of non-financial companies listed on Indonesia Stock Exchange in 2017. This study used purposive sampling and logistic regression analysis method to examine the relation between independent variable and dependent variable. This study showed that are a proxy from pressure variable in financial stability is asset change  has significant relation to financial statement fraud. And but a proxy external pressure is free cash flow and a proxy financial target is return on asset has not significant relation to financial statement fraud. And a proxy from opportunity variable in nature of industry and ineffective monitoring are receivable, committe audit, and independence committe audit has not significant relation to financial statement fraud.